Hours worked and patient visits provided by dentists in Australia. (2nd January 2018) - Brennan, DS; Chrisopoulos, S; Teusner, DN
Abstract: Background: The aim was to examine the numbers of hours worked and patient visits provided by age and gender of dentists in Australia, and compare with previous estimates to describe trends. Methods: Data were collected from a random sample (N = 2961) of Australian dentists. Private sector dentists working in clinical practise were included in the analysis. Results: The response rate was 49% (N = 1345 dentists). Hours per year worked and number of patient visits per year were lower for dentists aged 65 years and older compared with younger dentists, and were higher for male compared with female dentists aged 35–45 to 55–64 years. Hours per year worked were lower in 2013–2014 than reported in 2009–2010, but the number of patient visits in 2013–2014 was similar to the previously reported estimate from 2009–2010. Conclusions: Hours worked and visits provided were only lower among older dentists aged 65 years or more. Male dentists tend to work more hours per year and provide more patient visits per year than female dentists. Over the last decade, Australian dentists maintained a stable output of visits per year despite a trend towards fewer hours worked per year.